2008
DOI: 10.1038/ng.190
|View full text |Cite
|
Sign up to set email alerts
|

PTPRD (protein tyrosine phosphatase receptor type delta) is associated with restless legs syndrome

Abstract: We identified association of restless legs syndrome (RLS) with PTPRD at 9p23-24 in 2,458 affected individuals and 4,749 controls from Germany, Austria, Czechia and Canada. Two independent SNPs in the 5' UTR of splice variants expressed predominantly in the central nervous system showed highly significant P values (rs4626664, P(nominal/lambda corrected) = 5.91 x 10(-10), odds ratio (OR) = 1.44; rs1975197, P(nominal/lambda corrected) = 5.81 x 10(-9), OR = 1.31). This work identifies PTPRD as the fourth genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
3
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(204 citation statements)
references
References 15 publications
7
181
3
13
Order By: Relevance
“…33,34 Intriguingly, a recent genome-wide association study has implicated PTPRD as a locus for RLS. 35 Moreover, genetic variants of PTPRD associate with bronchial asthma, 36 which is reported to occur at higher rates in children with ADHD, 37 and RLS patients have been shown to have increased use of asthma medications. 38 Studies of the PTPRD gene in mice show high expression in the hippocampus, the only brain region reported to be enlarged in ADHD, 39 along with involvement in spatial learning, long-term potentiation and axonal guidance of motor neurons.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Intriguingly, a recent genome-wide association study has implicated PTPRD as a locus for RLS. 35 Moreover, genetic variants of PTPRD associate with bronchial asthma, 36 which is reported to occur at higher rates in children with ADHD, 37 and RLS patients have been shown to have increased use of asthma medications. 38 Studies of the PTPRD gene in mice show high expression in the hippocampus, the only brain region reported to be enlarged in ADHD, 39 along with involvement in spatial learning, long-term potentiation and axonal guidance of motor neurons.…”
Section: Resultsmentioning
confidence: 99%
“…4 RLS also has a considerable heritability and is associated with multiple genetic risk factors. Genome-wide association studies [5][6][7][8][9][10] identified variants in six loci encompassing the genes MEIS1, BTBD9, MAP2K5/SKOR1, PTPRD, and TOX3/non-coding RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Additional risk variants have been identifi ed recently, consisting of two single nucleotide polymorphisms (SNPs) expressed in the pro tein tyrosine phosphatase, receptor type, D ( PTPRD ) gene, a gene involved with neuronal development that may also provide a possible functional association. 27 The importance of these studies is that they point toward a molecular mechanism for this condition. Little is known at this time about the exact function of most of these genes and how they play a role in the development of RLS/PLMS.…”
Section: Restless Legs Syndrome and Periodic Limb Movements In Sleepmentioning
confidence: 99%